Effect Of 0.2% chlorhexidine gel in the management of postoperative pain afterpre-prosthetic surgery : pilot study = Efecto del gel de clorhexidina al 0.2% en el manejo del dolor postoperatorio después de unacirugía pre-protésica : estudio piloto - Marcín Montero, Claudina; Martínez Aguilar, Víctor Manuel; Castillo Bolio, Rubén; Mena Porras, Esteban 1999-; Pozos Guillén, Amaury de Jesús (2025)
Pre-prosthetic surgical procedures such as clinical crown lengthening (CLS), can cause pain, discomfort, and postoperative inflammation; causing the need of the prescription of medications such as analgesic, anti-inflammatories and in certain cases systemic antibiotics. However, prolonged and indiscriminate use of these medications often leads to adverse effects on general health. Thus, the ideal to treat locally pain and inflammation, and to prevent local infection is promising. The objective of this preliminary study was to evaluate the controlled use of a local chlorhexidine gel (CHXg) immediately place after pre-prosthetic periodontal surgery to manage postoperative pain using a customized whitening trays. A randomized controlled double-blind parallel-group clinical pilot trial was conducted. A sample of 10 patients aged 18 to 60 years, requiring a crown lengthening procedure was selected. Two groups (Group A: 0.2% CHXg vs Group B: placebo gel). Pain scores were evaluated by using a visual analog scale (VAS), and side effects and poswas 3.32 for Group A and 4.85 for Group B (p=0.05), with results showing no statistically significant difference. Few studies have assessed the effect and influence of 0.2% CHX gel on postoperative pain control. Some reports suggest that intra-alveolar use of CHX gel is more effective than administering 10 mg of ketorolac alone. In this study, there were no statistically significant differences, indicating that the use of 0.2% CHX gel applied after pre-prosthetic surgery may not significantly reduce postoperative pain.
Los procedimientos quirúrgicos preprotésicos, como el alargamiento clínico de la corona (ACC), pueden causar dolor, malestar e inflamación posoperatoria, lo que requiere la prescripción de medicamentos. Sin embargo, el uso prolongado e indiscriminado de estos medicamentos suele provocar efectos adversos en la salud general. El objetivo de este estudio es evaluar un sistema local de liberación controlada que utiliza gel de clorhexidina (CHX) posterior a cirugías preprotesicas periodontales para controlar el dolor posoperatorio, en comparación con un grupo de placebo. Se realizó un ensayo clínico aleatorizado, controlado, doble ciego, de grupos paralelos con múltiples dosis. Se seleccionó una muestra de 10 pacientes, con edades entre 18 y 60 años, que requerían un procedimiento de alargamiento de corona. Se formaron dos grupos: el grupo A recibió gel de clorhexidina (CHX) al 0,2% y el grupo B recibió un placebo. La puntuación media de la escala visual analógica (EVA) (en mm) fue de 3,32 para el grupo A y de 4,85 para el grupo B (p=0,05), y los resultados no mostraron diferencias estadísticamente significativas. Pocos estudios han evaluado el efecto y la influencia del gel CHX al 0,2% en el control del dolor posoperatorio. Algunos informes sugieren que el uso intraalveolar de gel CHX es más eficaz que la administración de 10 mg de ketorolaco solo. En este estudio, no hubo diferencias estadísticamente significativas, lo que indica que el uso de gel CHX al 0,2% aplicado después de la cirugía preprotésica puede no reducir significativamente el dolor posoperatorio.
En revista Odóvtos, Online First, 2025
Descripción basada en el contenido visto el 20 de marzo, 2025
También disponible en formato HTML y EPUB